2021
DOI: 10.3390/polym13244381
|View full text |Cite
|
Sign up to set email alerts
|

Self-Healable and Recyclable Biomass-Derived Polyurethane Networks through Carbon Dioxide Immobilization

Abstract: Due to growing environmental issues, research on carbon dioxide (CO2) use is widely conducted and efforts are being made to produce useful materials from biomass-derived resources. However, polymer materials developed by a combined strategy (i.e., both CO2-immobilized and biomass-derived) are rare. In this study, we synthesized biomass-derived poly(carbonate-co-urethane) (PCU) networks using CO2-immobilized furan carbonate diols (FCDs) via an ecofriendly method. The synthesis of FCDs was performed by directly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
(96 reference statements)
0
2
0
Order By: Relevance
“…Our group has previously reported that thermoplastic or thermoset polymers can easily be prepared using BHMF via a facile, solvent-free ball milling process and can be used for self-healable, reprocessable, and shape-memory materials [ 31 , 32 ]. However, synthetic strategies involving biomass- and CO 2 -derived monomers are still quite rare, despite the increasing number of reports on sustainable polymers fabricated from each renewable source [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our group has previously reported that thermoplastic or thermoset polymers can easily be prepared using BHMF via a facile, solvent-free ball milling process and can be used for self-healable, reprocessable, and shape-memory materials [ 31 , 32 ]. However, synthetic strategies involving biomass- and CO 2 -derived monomers are still quite rare, despite the increasing number of reports on sustainable polymers fabricated from each renewable source [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The growing consumption of crude oil on human development highlights the concern of the resource availability and environmental crisis. On this account, the renewable and sustainable polymeric materials have become a mainstream research topic [1][2][3]. The transformation of the traditional petro-based plastics to bio-based polymeric materials not only brings a new blueprint for resource richness, but also provides benefits to our environment [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%